Analysis of Students' Misconception of Grade XI on Buffer Solution Material Using Three-Tier Multiple Choice Diagnostic Test Instrument - Lifa Nur Aminatus Sholikhah; Rendy Priyasmika (Tarbiyah : Jurnal Ilmiah Kependidikan, 2025)
This study aims to analyze misconceptions experienced by grade XI students on buffer solution material using a three-tier multiple-choice diagnostic test instrument. Misconceptions are one of the obstacles in the learning process, especially on abstract chemical concepts such as buffer solutions. A three-tier multiple choice diagnostic test instrument allows for deeper detection of misconceptions and distinguishing between correct understanding and misconceptions. This study was conducted at MAN 2 Lamongan with research subjects of grade XI MIPA students. This quantitative descriptive study involves 40 grade XI MIPA students who have studied buffer solution material. Research data were collected through a three-tier multiple-choice diagnostic test instrument. Data processing uses a percentage calculation technique, which is then grouped into three categories of understanding: understanding the concept, misconceptions, and not understanding the concept. The study results showed that students' misconceptions of buffer solution material occurred in all concepts with an average percentage of 36.5%, which is included in the moderate misconception category. The lowest misconception was identified in the buffer solution concept, with a percentage of 30.73%. Meanwhile, the highest misconception identified was the concept of buffer solutions being essential, with a percentage of 41.52%.